2005
DOI: 10.3748/wjg.v11.i12.1737
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin as a protective factor in hepatic steatosis

Abstract: AIM: Obesity and insulin resistance (IR) are closely related to hepatic steatosis (HS), and adiponectin is a hepatic insulin sensitizer that has important effects in liver function. This study aims at investigating the relationship between serum adiponectin concentration and the presence of HS. METHODS:We carried out a cross-sectional study in a check-up unit of a University Hospital in Mexico City. We enrolled 196 subjects, comprising 98 subjects with HS (27 women, 71 men) and 98 controls (37 women and 61 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 34 publications
3
20
1
1
Order By: Relevance
“…52) Another GLP-1 analogue, exendin-4, has been demonstrated to decrease the fatty acid load in hepatocytes and reverse hepatic steatosis in obese mice. 53,54) In the present study, our results confirmed that liraglutide decreased body weight, increased insulin sensitivity, reduced hepatic lipid accumulation and consequently decreased serum ALT levels, which indicated that liraglutide might have a liver protective effect in the rats with HFHC diet-induced NAFLD. Previous studies have reported that MDA levels in the liver were reduced by administration of exendin-4 in ob/ob mice.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…52) Another GLP-1 analogue, exendin-4, has been demonstrated to decrease the fatty acid load in hepatocytes and reverse hepatic steatosis in obese mice. 53,54) In the present study, our results confirmed that liraglutide decreased body weight, increased insulin sensitivity, reduced hepatic lipid accumulation and consequently decreased serum ALT levels, which indicated that liraglutide might have a liver protective effect in the rats with HFHC diet-induced NAFLD. Previous studies have reported that MDA levels in the liver were reduced by administration of exendin-4 in ob/ob mice.…”
Section: Discussionsupporting
confidence: 76%
“…54) A large number of studies in experimental animals and patients have found that the level of adiponectin is closely related to obesity, insulin resistance, coronary heart disease and NAFLD. 55,56) In addition, adiponectin has been reported to be tightly associated with oxidative stress and inflammatory respons.…”
Section: Discussionmentioning
confidence: 99%
“…Diagn. 7(2), (2007) are significantly lower in NAFLD patients than in their matched controls [26,27]. This is also true for the patients with coronary artery disease [28].…”
supporting
confidence: 58%
“…2A, 10) were detected in CM. As hepatocyte growth factor, leptin, and adiponectin have been shown to act as protective factors against steatosis, [15][16][17] we investigated the effect of blocking antibodies against IL-6, GRO, IL-8, and MCP-1. Only anti-MCP-1 blocked CM-induced lipid accumulation in Huh-7 cells, albeit not completely (Fig.…”
Section: Of Human Scwat Explants Induces Significantmentioning
confidence: 99%